Cardiovascular Complications Following Acute Methadone Poisoning in Patients with and Without a History of Long-term Methadone Use - Gholamali Dorooshi; Mahbod Shirmohammadi; Farzad Gheshlaghi; Arman Otroshi; Shafeajafar Zoofaghari; Nastaran Eizadi-Mood (Journal of Research in Pharmacy Practice)
Objective: Given the prevalence of methadone poisoning, this study was conducted to compare the cardiovascular complications following acute methadone poisoning in patients with and without a history of long-term methadone use. Methods: In this retrospective study, information related to patients with acute methadone poisoning hospitalized at Al-Zahra and Khorshid hospitals in Isfahan-Iran was collected from hospital archives and analyzed. Patients were divided into two groups with and without a history of long-term methadone use. Findings: The mean of corrected QT interval (QTc), QRS, and heart rate showed no significant differences between the two groups at three-time points: baseline (upon admission), 12 h, and 24 h after admission (P > 0.05). The mean QT dispersion upon admission and 12 h after admission did not differ significantly between the groups (P > 0.05). However, the observation at 24 h postadmission indicated a significant increase in QT dispersion in the group with a history of long-term methadone use, showing a mean of 47.53 ± 10.62 ms compared to the without a history of long-term use group, with a mean of 26.78 ± 6.75 ms (P = 0.041). Conclusion: The results indicate that among the cardiovascular findings when analyzing the electrocardiograms of patients with acute methadone poisoning, only QT dispersion differed between patients with and without a history of long-term methadone use. Cardiovascular events resulting from methadone poisoning are the significant factors contributing to patient mortality, highlighting the need for the careful management of methadone use in these patients.